Realization of Social Technology through Maximizing the Implementation of the Digital Economy on Gross Domestic Product (GDP) of ASEAN Countries - Putra, M. Farash Abbiyan; Purnomo, Didit (Universitas Muhammadiyah Surakarta, 2023)
The objective of this research is to investigate the influence of social technology in fostering digital economic advancements and its consequential effects on the expansion of Gross Domestic Product (GDP) within the member nations of the Association of Southeast Asian Nations (ASEAN). This study focuses on the impact of the use of ICT for export activities (export ICT), the ICT index, and The impact of foreign direct investment (FDI) on the expansion of Gross Domestic Product (GDP) in ASEAN nations from 2014 to 2019. The employed analytical approach involves the utilization of Ordinary Least Squares (OLS), a technique that computes the data by employing the Chow test and the Hausman Random Effect Model (REM) test. The research results show that ICT exports do not have a significant effect on GDP, while the ICT index and foreign investment (FDI) have a significant effect on GDP. All independent variables have a significant influence on GDP. The fact that the use of ICT exports will not affect GDP growth. The significant impact of the ICT index on GDP growth is that the lower the ICT index, the more positive GDP growth, and the greater the foreign direct investment (FDI), the more significant GDP growth. The findings of this research can be used by policymakers to develop policies that encourage the implementation of the digital economy towards GDP growth.